Investigating the Influence of Infrastructure Development on Poverty in Emerging Markets - Tsaurai, Kunofiwa (EuroEconomica, 2024)
The positive role of infrastructure development in the economy is well defined, exhausted and conclusive. It is the empirical studies on the influence of infrastructure development on poverty which is still mixed, contradictory, divergent and far from being exhausted. This study contributes to literature by exploring the impact of infrastructure development on poverty alleviation in emerging markets. It also studied the influence of human capital development in the infrastructure development-poverty reduction nexus. Specifically, whether human capital development is a channel through which poverty alleviation is influenced by infrastructure development in emerging markets. The study used fixed effects and the dynamic GMM approach with panel data from 1993 to 2021. Fixed effects show that infrastructure development significantly reduced poverty when infant mortality and life expectancy were used as proxies. On the contrary, the dynamic GMM approach noted that infrastructure development non-significantly decreased poverty using life expectancy and infant mortality rate as measures of poverty. Emerging markets should therefore implement infrastructure development enhancement policies to alleviate poverty. Fixed effects indicate that the interaction between infrastructure and human capital development significantly reduced poverty across all the three measures of poverty. The dynamic GMM however found out a non-significant poverty alleviating impact influenced by the interaction between infrastructure and human capital development (when infant mortality rate and life expectancy proxies of poverty are used). Emerging markets should implement joint human capital and infrastructure development policies to enhance poverty alleviation. The study also encourages future empirical research on exploring threshold levels of infrastructure development necessary to significantly improve poverty alleviation. It also encourages investigating human capital development threshold levels that helps infrastructure development to significantly alleviate poverty in emerging markets.